1993
DOI: 10.1136/gut.34.11.1593
|View full text |Cite
|
Sign up to set email alerts
|

Expression of intercellular adhesion molecule 1 (ICAM-1, CD54) in colonic epithelial cells.

Abstract: The expression of intercellular adhesion molecule-I (ICAM-1, CD54)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
71
2
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 27 publications
8
71
2
2
Order By: Relevance
“…Moreover, several lines of evidence have demonstrated that IFN-␥ enhances ICAM-1 expression on intestinal epithelial cells (41)(42)(43)(44)(45). In line with this observation, we observed that ICAM-1 expression was enhanced in the ileum of WT, but not IFN-␥ KO, mice treated with toxin A.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, several lines of evidence have demonstrated that IFN-␥ enhances ICAM-1 expression on intestinal epithelial cells (41)(42)(43)(44)(45). In line with this observation, we observed that ICAM-1 expression was enhanced in the ileum of WT, but not IFN-␥ KO, mice treated with toxin A.…”
Section: Discussionsupporting
confidence: 89%
“…31,3638 Consistent with this, transfection of ICAM-1 into colorectal cancer cell lines inhibits tumor growth and metastasis. 39 In addition, the production of prostaglandin E2 in the tumor microenvironment downregulates the expression of ICAM-1 in tumor cells, reducing the cytotoxic effects of T cells.…”
Section: Discussionsupporting
confidence: 60%
“…14,15 In contrast, ICAM-1 is expressed both by the tumor endothelium as well as by tumor cells themselves. 16,19,20 Increased expression of ICAM-1 has been seen in tissue samples of breast carcinomas and is associated with an improved prognosis. 36 The mechanisms by which ICAM-1 expression leads to decreased tumor size are unknown, but may involve localization of leukocytes to the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ICAM-1 is expressed both by tumor endothelium as well as by tumor cells of epithelial origin. 16,19,20 This has been demonstrated using both tissue sections as well as tumor cell lines. Many have speculated that ICAM-1 and VCAM-1 expression may favor adhesive interactions with leukocytes, thus facilitating leukocyte tumor infiltration.…”
mentioning
confidence: 90%